Optimalisasi Pelayanan Masyarakat di Kelurahan Kilasah Kecamatan Kasemen Kota Serang dalam Mencapai Good Government - Ulinnuha Ulinnuha; Aini Pungki Sri Rahayu; Rahayu Yunitasari; Anugrah Alamsyah; Hotman Binsar Siregar (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Community services that do not run optimally result in obstruction of the government regulatory system in the agency. It can also cause fatal problems, such as increasing complaints from people who experience inconvenience and their service rights are not fulfilled. In principle, community service is a determining factor in the quality of government and the welfare of all sub-district officials and the community. This happened in various subdistrict agencies in various regions, including in Kilasah Subdistrict, Kasemen District, Serang City. As for the physical condition of the Killah sub-district office, it still does not have a permanent and independent sub-district office building, limited competent human resources, minimal facilities and infrastructure, minimal number of community service administration staff. So this Community Service activity aims to help optimize community services in Kilasah Village. The steps taken in implementation are the observation, preparation, implementation and evaluation stages.This community service (PkM) activity runs smoothly, the PkM team can assist in community services such as compiling sub-district correspondence, assisting in collecting data on poor people for social service events, collecting data on MSME actors for assistance in making NIBs and product branding, create social media accounts for online community service, and as a forum for citizens' aspirations in an easy way, as well as other administration . This can realize the role of the Kilasah Subdistrict government as a progressive, innovative and optimal service provider. So that we can achieve the ideals of Good Government that are aspired to by all governments, especially Kilasah Village